Neighborhood Environment and Falls among Community-Dwelling Older Adults - Nicklett, Emily Joy (Int J Environ Res Public Health, 2017)
Background: Falls present a major challenge to active aging, but the relationship between neighborhood factors and falls is poorly understood. This study examined the relationship between fall events and neighborhood factors, including neighborhood social cohesion (sense of belonging, trust, friendliness, and helpfulness) and physical environment (vandalism/graffiti, rubbish, vacant/deserted houses, and perceived safety walking home at night). Methods: Data were analyzed from 9259 participants over four biennial waves (2006–2012) of the Health and Retirement Study (HRS), a nationally representative sample of adults aged 65 and older in the United States. Results: In models adjusting for demographic and health-related covariates, a one-unit increase in neighborhood social cohesion was associated with 4% lower odds of experiencing a single fall (odds ratio (OR): 0.96, 95% confidence interval (CI): 0.93–0.99) and 6% lower odds of experiencing multiple falls (OR: 0.94, 95% CI: 0.90–0.98). A one-unit increase in the physical environment scale was associated with 4% lower odds of experiencing a single fall (OR: 0.96, 95% CI: 0.93–0.99) and with 5% lower odds of experiencing multiple falls (OR: 0.95, 95% CI: 0.91–1.00) in adjusted models. Conclusions: The physical and social neighborhood environment may affect fall risk among community-dwelling older adults. Findings support the ongoing need for evidence-based fall prevention programming in community and clinical settings.